Penerapan Model Cooperative Learning Tipe Make a Match Berbantuan Media Smart Box untuk Meningkatkan Pemahaman Belajar Murid dalam Materi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Kelas IV SDN 16 Sampoddo Palopo (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Students' understanding in Islamic Religious Education and Character Building lessons needs to be enhanced through active learning. This study aims to describe the implementation of the "Make A Match" cooperative learning model—supported by "Smart Box" media—and the resulting improvement in understanding among fourth-grade students at SDN 16 Sampoddo, Palopo. The study employed the Kemmis and McTaggart Classroom Action Research model across two cycles, comprising planning, action, observation, and reflection. Data were collected through tests, observations of teacher and student activities, and documentation, then analyzed both qualitatively and quantitatively. The results indicate that implementing this model improved student understanding. Learning mastery increased from 79% in Cycle I to 92% in Cycle II. Student activity rose from 68.75% to 84.38%, while teacher activity increased from 76.68% to 80.66%. Thus, the "Make A Match" model, supported by "Smart Box" media, is effective in enhancing student understanding and engagement in Islamic Religious Education and Character Building lessons.